Changes in postural stability induced by a ball-and-board game designed from a systems perspective - Anaëlle Cheillan; João Milho; Pedro Passos (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Postural behavior can be understood from a systems perspective, emerging from complex interactions within the agent’s body system and the agent-environment system, where inherent variability enables adaptive and functional solutions to balance perturbations. Recent studies have recommended that lower limbs rehabilitation programs should be addressed from a systems perspective for both clinical assessment and intervention. In this context, we designed a ball-and-board game that fosters interactions between the lower limbs and between the agents through informational and mechanical couplings. The present paper aims to investigate whether such a game – designed from a systems perspective – has an impact on an agent’s postural stability – using variability measures – also derived from a systems perspective. Methods Twenty-four novice participants were randomly assigned to twelve dyads to perform our game, which consists in a joint-action task where two participants stand on an unstable surface (BOSU) while jointly manipulating a board on which a ball rolls along a circular target. Body and ball’s three-dimensional movements were obtained using an 8-camera motion capture system. Postural stability was assessed using both linear and nonlinear measures, which respectively capture the amount and structure of variability in the center of mass’ kinematics. Additional between-subject analyses were conducted to study relationships between postural stability and task performance. Results Despite the heterogeneous postural pathway of the participants, significant postural changes occurred with practice (i.e., decreased standard deviation and increased sample entropy of postural oscillation variability) in the anteroposterior plane, which is also the plane of motion where the knee joint is predominantly engaged through flexion-extension movements. Participants with higher performance were characterized by a greater complexity in their postural oscillations (i.e., greater sample entropy), allowing an increased ability to resist to perturbations that threaten postural stability. Conclusions The amount of variability in postural oscillations evolved heterogeneously across participants, which suggests a broad exploration of different postural solutions and therefore an enhanced adaptability to balance perturbations. This adaptability was particularly evident in participants with higher performance, whose postural oscillations exhibited a less periodic, and thus more complex, variability structure. In conclusion, our game led to a postural reorganization that encourages us to test it in clinical settings.